Dataset on the expression "Canadian model" in the Swedish Press and student papers (2021-2023) - Premat, Christophe (Stockholm University, 2024)
This dataset is part of a study exploring representations of the "Canadian model" in Swedish media and among students enrolled in Canadian Studies courses at Stockholm University. The data covers media articles, radio transcripts, and anonymized student essays collected between 2021 and 2023. It includes qualitative and quantitative content, focusing on discourse analysis of how the "Canadian model" is portrayed in social, political, and academic contexts.

Swedish Media Corpus (2021-2023):
This section contains articles from various Swedish newspapers as well as radio transcripts that mention the "Canadian model" or similar terms such as "kanadensisk modell" and "kanadensisk förebild." The media content was sourced from the Mediearkivet database and the National Library of Sweden. The list of articles (from Mediearkivet) is present but for copyright issues, we were not allowed to attach the whole articles.

Student Papers on Canadian Studies (2021-2023):
This section includes anonymized essays written by students from Stockholm University as part of an introductory course on Canadian Studies. Each essay engages with the concept of the "Canadian model," responding to a quote from Canadian Prime Minister Justin Trudeau. The student papers are available in text format (PDF/Word) and are provided with metadata that includes the year of submission and the total word count. The collection comprises a total of 155,692 words across 87 student essays. This dataset is available for academic research purposes under the terms of a Creative Commons license. All data has been anonymized in accordance with GDPR principles, and no personal identifiers are included. A course plan corresponding to the course at the basic level has also been added.
Keywords: Cultural studies not elsewhere classified; Cultural Studies; Kulturstudier